DESKRIPSI PEMAHAMAN TOLERANSI BERAGAMA SISWA KATOLIK KELAS XII SMA KOLESE DE BRITTO - Putri, Armita Eka; Hendra, Alexander (CREDENDUM: Jurnal Pendidikan Agama, 2024)
Religious tolerance in De Britto High School, Yogyakarta has been developed through curricular and cultural approaches. Religiosity education as a model of religious education in De Britto High School is considered as curriculum approach for tolerance. This approach is supported by several interreligious activities for tolerance conducted by Campus Ministry, such as, interreligious live-in and visiting religious communities. As a Catholic school, De Britto is deeply influenced by Catholic values. This is show in their visions and missions, activities and teachers. One of the interesting facts is that both of the religiosity education teachers are Catholics which certainly influence the way of understanding tolerance. This research aims at describing how students at De Britto High School perceive and understands religious tolerance. To collect the data, researcher employs on observation, interview and Focus Group Discussion. This research uses purposive sampling with some criteria to select informants, such as, Catholic students of class XII, who are active in learning process, and have a broad and open perspective. Based on the data analysis, researcher found three themes. First, tolerance is understood dynamically as both active and passive. Passive tolerance is understood as non-interference tolerance where people are staying in their ghettos. Meanwhile, active tolerance refers to collaboration for common good. Second, tolerance is part of Catholic education influenced by Jesuit perspective which has been the main vision in De Britto High School as a Jesuit school in Yogyakarta. Third, tolerance is part of interreligious dialogue.